Effect of SIS3 on Extracellular Matrix Remodeling and Repair in a Lipopolysaccharide-Induced ARDS Rat Model - Qiong Liang; Qiqing Lin; Yueyong Li; Weigui Luo; Xia Huang; Yujie Jiang; Chunyan Qin; Jin Nong; Xiang Chen; Suren Rao Sooranna; Liao Pinhu (Journal of Immunology Research)
The remodeling of the extracellular matrix (ECM) in the parenchyma plays an important role in the development of acute respiratory distress syndrome (ARDS), a disease characterized by lung injury. Although it is clear that TGF-β1 can modulate the expression of the extracellular matrix (ECM) through intracellular signaling molecules such as Smad3, its role as a therapeutic target against ARDS remains unknown. In this study, a rat model was established to mimic ARDS via intratracheal instillation of lipopolysaccharide (LPS). A selective inhibitor of Smad3 (SIS3) was intraperitoneally injected into the disease model, while phosphate-buffered saline (PBS) was used in the control group. Animal tissues were then evaluated using histological analysis, immunohistochemistry, RT-qPCR, ELISA, and western blotting. LPS was found to stimulate the expression of RAGE, TGF-β1, MMP2, and MMP9 in the rat model. Moreover, treatment with SIS3 was observed to reverse the expression of these molecules. In addition, pretreatment with SIS3 was shown to partially inhibit the phosphorylation of Smad3 and alleviate symptoms including lung injury and pulmonary edema. These findings indicate that SIS3, or the blocking of TGF-β/Smad3 pathways, could influence remodeling of the ECM and this may serve as a therapeutic strategy against ARDS.